“Eu vim buscar macaxeira e inhame”: uma experiência entre beneficiárias do programa de aquisição de alimentos (PAA) em Rio Tinto/PB - Pinto, Luana Maia (2018)
Food and nutritional security is the subject of a wide debate about the main objectives of planning and building public policies in Brazil. The Food Acquisition Program (PAA) was created in 2003, at the beginning at Lula's government, as part of the Fome Zero program. Among the main objectives, the action seeks to ensure access to food by people living in conditions of food and/or nutritional insecurity, also encouraging family farming through government food purchases. The “purchase with simultaneous donation” modality, part of what forms the PAA, was the action that I had the opportunity to get to know and experience. During the development of this work - between the years 2017 and 2018 - I set out to accompany the movement of the Social Assistance Reference Center (CRAS) in the municipality of Rio Tinto/PB, in order to observe the various relationships that take place within this and analyze the meanings associated with the practice of social policies. The ethnography carried out contributed to the data collection, starting from the coexistence and execution of the program with the group of beneficiaries and servers of CRAS. Presenting the ways of acting and the relationships between state actors and society, I try to highlight some discussions related to gender visibility, social and family matrix, poverty and vulnerability. Despite being conceptually inaccurate, the term social vulnerability reinforces the understanding of the various factors that weaken subjects in the exercise of their citizenship. This effective follow-up of a program aimed at food and nutrition security is based on analytical support for issues related to government technologies, devices, biopower and biopolitics. Social Assistance policies can be thought of as a network where one action will be linked to others. Therefore, by researching the PAA and entering into the common life of these women beneficiaries, I was able to learn how these actions are linked to the management of the life of their family group.